TCAD Modeling of Surface Radiation Damage Effects: A State-Of-The-Art Review - Morozzi, Arianna; Moscatelli, Francesco; Croci, Tommaso; Passeri, Daniele (Frontiers in Physics, 2021)
A comprehensive numerical model which accounts for surface damage effects induced by radiation on silicon particle detectors is presented with reference to the state-of-the-art Synopsys Sentaurus Technology CAD (TCAD) tool. The overall aim of this work is to present the “Perugia 2019 Surface” damage modeling scheme, fully implemented within the TCAD environment, which effectively describes the surface damage effects induced by radiation in silicon sensors relying on a limited number of parameters relevant for physics. To this end, extensive measurement campaigns have been recently performed on gated-diodes and MOS capacitors at Fondazione Bruno Kessler (FBK) in Italy, Hamamatsu Photonics (HPK) in Japan and Infineon Technologies (IFX) in Austria on both n-type and p-type substrates (with and without p-spray isolation implants), in order to extrapolate the relevant parameters which rule the surface damage effects. The integrated interface trap density and the oxide charge density, have been determined before and after X-ray irradiation with doses ranging from 0.05 to 100 Mrad(SiO2), for each specific foundry and technology flavor. The main guidelines of this study are the versatility and generality of the simulation approach.